INAPLICABILIDAD DE LA LEY FRENTE A LA DESAPARICIÓN FORZADA DE PERSONAS EN EL ECUADOR Y SU INCIDENCIA EN EL DERECHO INTERNACIONAL - Sánchez Rojas, Jefferson Rodrigo (2018)
The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in The elaboration of this legal research work was motivated by the fact that in Ecuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearancEcuador has been forced disappearanc Ecuador has been forced disappearancEcuador has been forced disappearance of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem e of people, a very serious problem that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to that attacks society in general, is why we have seen the need to investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the investigate this problem. Most of these cases have not been resolved by the Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not Ecuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for notEcuadorian justice system since the judicial is ineffective for not complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced complying with current regulations to resolve these cases of forced disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve disappearance of persons, and as a consequence the failure to resolve internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before internally, the next of kin these disappeared persons go before international justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they are international justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they are international justice agencies so that they are international justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they are international justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they are international justice agencies so that they are international justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they areinternational justice agencies so that they are the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and the ones who investigate and solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, solve these cases. In order to determine that problem, a conceptual, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, doctrinal, legal and comparative law investigation has been carried out, analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with analyzing this type of crime, carrying out surveys and interviews with specialists o specialists ospecialists o specialists o specialists or legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and r legal professionals so that the objectives can be verified and the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that the hypothesis put forward can be tested. which led to conclusion that Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, Article 84 of the Comprehensive Criminal Code must reform article, adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sanctiadding that the public servant must be sancti adding that the public servant must be sanctiadding that the public servant must be sancti oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and oned with the dismissal and absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, absolute disqualification of his position or function that he had been fulfilling, in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created in the same way as General Prosecutor's Office of State is created a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wi a Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this wia Specialized Unit for the forced disappearance of persons, this with the th the th the th the th the purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are purpose that the law is fulfilled and cases have not been solved are investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity. investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity.investigated and thus they do not remain in impunity. investigated